Effect of inorganic phosphorus on repeat breeding crossbred cows - ASTHANA, R K; ROY, G P; AKHTAR, M H; PANDEY, R P; SINGH, A P; KUMAR, NIRAJ (The Indian Journal of Animal Reproduction, 2007)
A study was conducted on 70 repeat breeding cross bred cows. 20 cows (Cl) served as healthy control. Repeat breeding cow were divided in to six groups i.e. 10 cow as untreated control (C2) and treatment group. Treatment groups T1 having 20 cows and rest (T2-T5) 10 cow each. each groupreceived treatment as mineral mixture (T1) , Duraprogen- Progesterone(T2) , lliren- Prostaglandin {T3),Amikacin(T4) and Oxytetracyclin (T5) . On Oday of estrus mean value of serum inorganic phosphorusranged from 4.48 to 5.86mg% whereas the values for different groups were found to be as C2(4.85),T1(4.84), T2(5.0.8), Ti5.07), T5(5 .00) mg%, and were less than the normal healthy control (5.90mg%).On day 21 the serum inorganic phosphorus value decreased (P
Keywords: Inorganic Phosphorus; Repeat breeding; Mineral mixture